Elevated cerebrospinal fluid (CSF) leptin in idiopathic intracranial hypertension (IIH): evidence for hypothalamic leptin resistance? - Ball, A; Sinclair, A; Curnow, S; Tomlinson, J; Burdon, M; Walker, E; Stewart, P; Nightingale, P; Clarke, C; Rauz, S (2009)
OBJECTIVE: The aetiology of idiopathic intracranial hypertension (IIH) is not known, but its association with obesity is well-recognized. Recent studies have linked obesity with abnormalities in circulating inflammatory and adiposity related cytokines. The aim of this study was to characterize adipokine and inflammatory cytokine profiles in IIH. DESIGN: Paired serum and cerebrospinal fluid (CSF) specimens were collected from 26 patients with IIH and compared to 62 control subjects. Samples were analysed for leptin, resistin, adiponectin, insulin, IL-1beta, IL-6, IL-8 (CXCL8), TNFalpha, MCP-1 (CCL2), hepatocyte growth factor, nerve growth factor and PAI-1 using multiplex bead immunoassays. RESULTS: CSF leptin was significantly higher in patients with IIH (P = 0.001) compared to controls after correction for age, gender and body mass index (BMI). In the control population, BMI correlated with serum leptin (r = 0.34; P = 0.007) and CSF leptin (r = 0.51; P < 0.0001), but this was not the case for the IIH population. Profiles of other inflammatory cytokines and adipokines did not differ between IIH patients and controls once anthropometric factors had been accounted for. CONCLUSIONS: IIH was characterized by significantly elevated CSF leptin levels which did not correlate with BMI. We suggest that CSF leptin may be important in the pathophysiology of IIH and that obesity in IIH may occur as a result of hypothalamic leptin resistance.